Penerapan Metode Agile Dalam Sistem Informasi Manajemen Asrama Santri pada Yayasan Pondok Pesantren Darul Huda Blitar Berbasis Web - Mawaddah, Udkhiati; Wahyuni, Ervika Dewi; Kusuma, Abdi Pandu (J-INTECH (Journal of Information and Technology), 2023)
The Darul Huda Blitar Islamic boarding school foundation is a boarding school that has many students. Currently data collection on students and dormitory management is still manual, there is no technology in the form of an information system so the boarding school administrators have difficulty controlling the number of students so that the ratio of the number of rooms and the number of students in each room is balanced. Website-based information systems are an option that is quite effective in making it easier for organizations or institutions to make data and decisions that are connected via the internet. This research aims to develop an information system for foundation boarding school management at the Darul Huda Blitar Islamic boarding school using the agile system development method. The agile method has the following stages starting from planning, analysis and design, implementation, testing, evaluation, completion and improvement. The results of this research are a web-based student dormitory management information system which is in line with expectations and with a few improvements to the appearance, this system will be very useful in assisting Islamic boarding school management.